ERBB and P‐glycoprotein inhibitors break resistance in relapsed neuroblastoma models through P‐glycoprotein. Issue 1 (5th November 2022) - Rösch, Lisa; Herter, Sonja; Najafi, Sara; Ridinger, Johannes; Peterziel, Heike; Cinatl, Jindrich; Jones, David T. W.; Michaelis, Martin; Witt, Olaf; Oehme, Ina
Abstract : Chemotherapy resistance is a persistent clinical problem in relapsed high‐risk neuroblastomas. We tested a panel of 15 drugs for sensitization of neuroblastoma cells to the conventional chemotherapeutic vincristine, identifying tariquidar, an inhibitor of the transmembrane pump P‐glycoprotein (P‐gp/ ABCB1 ), and the ERBB family inhibitor afatinib as the top resistance breakers. Both compounds were efficient in sensitizing neuroblastoma cells to vincristine in trypan blue exclusion assays and in inducing apoptotic cell death. The evaluation of ERBB signaling revealed no functional inhibition, that is, dephosphorylation of the downstream pathways upon afatinib treatment but direct off‐target interference with P‐gp function. Depletion of ABCB1, but not ERRB4, sensitized cells to vincristine treatment. P‐gp inhibition substantially broke vincristine resistance in vitro and in vivo (zebrafish embryo xenograft). The analysis of gene expression datasets of more than 50 different neuroblastoma cell lines (primary and relapsed) and more than 160 neuroblastoma patient samples from the pediatric precision medicine platform INFORM (Individualized Therapy For Relapsed Malignancies in Childhood) confirmed a pivotal role of P‐gp specifically in neuroblastoma resistance at relapse, while the ERBB family appears to play a minor part. Abstract : Chemotherapy resistance is a clinical problem in relapsed neuroblastomas (NBs). With a vincristine (VCR, yellow symbol) resistant model (A), we identified tariquidar (green), an inhibitor of the efflux pump P‐gp/ ABCB1, and afatinib (orange), an ERBB inhibitor, as resistance breaker (B). The comprehensive analysis of ERBB4 and P‐gp/ ABCB1 expression and function (C), revealed that both drugs act through P‐gp inhibition (D).